Fa’aliyyatu Kitab al-‘Ashri fi Tarqiyyati al-Maharah al-Lughawiyyah - Siti Mahmudah (Jurnal Internasional Pendidikan Bahasa Arab, 2021)
The purpose of this study was to determine the effectiveness of the book al-'Ashri in improving the Arabic language skills of fourth grade students at SD Muhammadiyah Metro for the 2019/2020 academic year. For this reason, the researcher collected the required data using several data collection methods, namely tests, interviews, observation and documentation. After the data was collected, the researcher analyzed the data using the "ANOVA" formula, then continued with the "t" test and the calculation of data analysis is calculated using spss. The results of this study indicate that there is a significant effect of the application of the book Al 'asri to improve the language skills of fourth grade students of SD Muhammadiyah Metro Pusat. Based on the output "statistical test" it is known that the value of asyimp sig (2-tailed) is 0.0000, for listening skills is 0, 006, speaking skills is 0.000, reading skills is 0, 005, writing skills is 0, 0392 and for other aspects knowledge 0, 000. All of these values ​​are smaller than the probability value of 0, 05 so it can be concluded that Ha is accepted.